Parenting Styles and Self-Efficacy Among Parents Raising Children with Special Needs in Selected Areas in Quezon City: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research determines the influence of parenting styles on the parents and how children are raised, especially In this paper, the researcher attempts to bring an original contribution through the identification and completion of the missing literature—offering recommendations for future research on the role of parents in shaping the future of their children.  Much research has been done on parents' role in shaping their children's future. However, more comprehensive research needs to be conducted on the role of parents and different parenting styles on their children’s behaviour. This study refers to the relationship between Parenting styles and self-efficacy among parents raising their children with special needs. Researchers used the Statistical Package for the Social Sciences as a statistical tool (SPSS). SPSS is a statistical software package that researchers use to analyze complex statistical data. The research used Pearson's Correlation Coefficient statistic to determine the statistical relationship between two continuous variables. It is regarded as the best approach for determining the relationship between two variables of interest due to its reliance on the covariance method. It contains information about the degree of the association, or correlation, and its direction. This study shows that parenting styles and self-efficacy correlate. Parents execute the behavior towards their children.
Keywords: Parenting style; Authoritarian; Neglectful; Authoritative Permissive; Special Needs; Self-efficacy